PENGEMBANGAN E-LKPD BERNUANSA ESQ (EMOTIONAL SPIRITUAL QUOTIENT) PADA MATERI PROTISTA KELAS X SMA - Melandi Wimudi; Sa’diatul Fuadiyah; Zulyusri Zulyusri; Helsa Rahmatika; Azwir Azwir (Bioilmi: Jurnal Pendidikan, 2022)
The use of instructional media at Adabiah 2 Padang High School is not maximized and the biology learning process is still focused on intellectual intelligence, even though there are other intelligences that must be possessed by students, namely spiritual and emotional intelligence. Material that is considered difficult by students in learning biology is protist material. This research is a development research using the 4-D Model (define, design, develop, disseminate) which is limited to the develop stage. This study aims to produce e-LKPD with ESQ nuances on protist material that is valid and practical. The research subjects were two biology lecturers at FMIPA UNP, one biology teacher at Adabiah 2 Padang High School, and 30 students in class X MIPA at Adabiah 2 Padang High School. The data collection instruments used were teacher interview questionnaires, student observation questionnaires, validity test questionnaires and practicality test questionnaires. Based on the results of the validity test, the percentage of e-LKPD with ESQ nuances was 86.4% with valid criteria while the average practicality test results by teachers and students were 85.8% with very practical criteria, so that the developed e-LKPD fulfilled criteria and can be used by students in learning biology.